ASIAN VALUES DI SINGAPURA (STUDI TENTANG PERAN KONFUSIANISME DALAM KEMAJUAN POLITIK SINGAPURA) - Anna Yulia Hartati (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2018)
This article research results that describe the role of Confucianism in Singapore's politicaladvancement. The assumption that Asian values are eroded by Western values is not provenin Singapore. Confucianism extracted into The Shared Values evolved into a national identityand became the basis for the life of a state and society in Singapore. The role ofConfucianism is vital in Singapore's political progress because of one main thing, namely touphold the interests of the nation and state. When the interests of the nation and state areplaced as a priority, the community feels as one entity that strives to maintain national unity,maintain harmony, and advance aspects of the country's life. This research uses documentaryresearch instrument, using library research technique (library research), that is by takingdata from books, articles, and internet. Design in this research use descriptive design, whilethe analysis using Constant Comparison (Grounded Theory Research).Keywords: Confucianism, The Shared Values, political progress